PELATIHAN PENINGKATAN LITERASI KEUANGAN BAGI REMAJA MASJID SEBAGAI UPAYA PENGEMBANGAN BADAN USAHA MASJID DI DESA KARYAMEKAR, PASIRWANGI KAB. GARUT - Eka Ahadiyat Suryana; Amna; Saepul Bahri; Agus Wibowo; Ira Mariyah Ulfah (POLITEKNIK LP3I JAKARTA, 2025)
This Community Service Program (PKM) aims to improve financial literacy among mosque youth as an effort to develop the Mosque Business Unit (BUM) in Karyamekar Village, Pasirwangi District, Garut Regency. The training was conducted on November 14–15, 2025 at Classroom 2 of SDN Karyamekar 2, attended by 26 participants consisting of Linmas, mosque youth, and LPM members. The program used interactive lectures, group discussions, financial recording simulations, and practical exercises to develop simple business plans. Results show an increase in participants’ understanding of financial management, transaction recording, and mosque-based business planning. Participants were able to create simple business plans supporting mosque economic independence. This activity positively impacts the capacity of mosque youth as community economic empowerment agents